PENGARUH PASTA GIGIMENGANDUNG MINYAK ATSIRI BUAH KAPULAGA MENGURANGI KADAR BAU MULUT: Effect of Pasta Containing Fruit Essential Oil Cardamom (Amomum cardamomum) against Pasta Users Teeth to Reduce Levels of Bad Breath in Sufferers Diabetes - Asri Yuniarta Saragih; Suci Erawaty (Jurnal Online Keperawatan Indonesia, 2020)
Problems regarding dental and oral disease still need serious attention to this day, including halitosis (bad breath). Bad breath is a symptom of an unconscious disorder or disease. For people with diabetes mellitus there is a decrease in salivary production, so Candida albicans and other species can increase in number in the oral cavity and eventually cause bad breath. One control of bad breath using toothpaste containing cardamom essential oils (Amomum cardamomum). The purpose of this study was to determine the effect of toothpaste containing cardamom essential oils (amomum cardamomum) on decreasing levels of bad breath in diabetics. This research is an experimental research with cross sectional design. The total sample of 30 people was taken by non random with purposive sampling. The analytical test used is Wilcoxon. In the study, the average halitosis levels before and after using toothpaste containing cardamom essential oils (Amomum cardamomum) were 115.33 ± 49.723 and 100.17 ± 47.206. The conclusion of this study is that there is an effect of pasta containing cardamom (Amomum cardamomum) essential oils on toothpaste users to reduce levels of bad breath in diabetics.